Nuevas observaciones de lectura de una matriz de molde para crustula de Aquincum - Mayer i Olivé, Marc (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The paper examines again a form of the well-known crustula from Aquincum, and suggests some new possibilities for various readings of the lectio vulgata.